2021
DOI: 10.1038/s41598-021-93846-w
|View full text |Cite
|
Sign up to set email alerts
|

Long-chain polyunsaturated fatty acid (LC-PUFA) status in severe preeclampsia and preterm birth: a cross sectional study

Abstract: Long-Chain Polyunsaturated Fatty Acid (LCPUFA) is essential throughout pregnancy, since deficiency of LPUFA may linked to obstetrical complications. This study aimed to investigate LCPUFA status in severe preeclampsia and preterm birth. A cross sectional study was conducted in 104 pregnant women, which divided into normal pregnancy, severe preeclampsia and preterm birth groups. Serum percentage and concentration of total LCPUFA, omega-3, alpha-linolenic acid (ALA), eicosapentaenoic acid (EPA), docosahexaenoic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
2
13
0
1
Order By: Relevance
“…PUFAs are mainly localized in cytoplasmic membranes and are degraded for energy generation through the citric acid cycle and ketogenesis. Despite the known beneficial effects of omega-6 and omega-3, in patients with HDP, long-chain polyunsaturated fatty acids are thought to increase the risk of preeclampsia and preterm birth ( Irwinda et al, 2021 ). Furthermore, 2-hydroxyvalerate was also noted to be increased in patients with HDP.…”
Section: Discussionmentioning
confidence: 99%
“…PUFAs are mainly localized in cytoplasmic membranes and are degraded for energy generation through the citric acid cycle and ketogenesis. Despite the known beneficial effects of omega-6 and omega-3, in patients with HDP, long-chain polyunsaturated fatty acids are thought to increase the risk of preeclampsia and preterm birth ( Irwinda et al, 2021 ). Furthermore, 2-hydroxyvalerate was also noted to be increased in patients with HDP.…”
Section: Discussionmentioning
confidence: 99%
“…A single-cell transcriptomics of the human placenta analysis indicated LPCAT3 and Sat1 (spermidine/ spermine N1-acetyltransferase 1) highly expressed in trophoblasts (Ng et al, 2019), both of which are related to ferroptosis (Dixon et al, 2015;Ou et al, 2016). Irwinda, R., et al reported that the level of PUFAs significantly increased in PE patients (Irwinda et al, 2021;Liao et al, 2022). Furthermore, in rats model of PE, the concentration of MDA, the end product of lipid peroxidation, in the placenta has increased dramatically (Zhang et al, 2020).…”
Section: Pre-eclampsiamentioning
confidence: 99%
“…This result suggests that low plasma DHA and EPA concentrations during pregnancy may be a strong risk factor for preterm birth. A cross-sectional study in 2021 also suggested that the plasma DHA levels of PT pregnant women at delivery were significantly lower than those of full-term pregnant women [ 17 ]. However, this study did not compare the plasma DHA levels of PT pregnant women at delivery with the plasma DHA levels of full-term pregnant women at the corresponding gestational weeks, and there is no study to dynamically monitor the changes in plasma DHA levels of pregnant women throughout the whole pregnancy, so it is not possible to confirm whether the results are caused by different gestational weeks.…”
Section: Preterm Birth (Pt)mentioning
confidence: 99%
“…Therefore, maternal DHA intake and placental transport function are critical for fetal DHA acquisition [ 15 ]. However, in some pregnancy complications, low maternal DHA levels [ 16 , 17 ] or dysfunction in placental fatty acid transport [ 18 , 19 ] leads to DHA deficiency in the offspring, which may lead to long-term neurological disorders. Thus, women with pregnancy complications may benefit from DHA supplementation.…”
Section: Introductionmentioning
confidence: 99%